THE EFFECT OF METFORMIN AND GLIMEPIRIDE ON PLATELET COUNT AND INDICES AMONG DIABETIC PATIENTS WERE ATTENDING JABER ABU ALIZ DIABETIC CENTER IN KHARTOUM STATE - Hussein, Hussein Abker; Elmagzoub, Fatima-Elzhra Ahmed; Babikir, Dalia Mohammed; Samaan, Mouna Adel (Journal of Biomedical and Pharmaceutical Research, 2021)
Diabetes mellitus (DM) is a global pandemic, Platelets have crucial role in accelerated atherosclerosis and thrombosis which characterize DM. Aim The aim of the study was to detect the effect of two major oral hypoglycemic drugs (Metformin and Glimepiride) on platelet count and indices MPV (Mean platelet volume), PLCR (platelet large cell ratio),PDW (platelet distribution width).Beside, to studythe effects of variation induration of the drug, dose of drug, HbA1C level and associated complications. Material and methods A case control study was performed 146subjects 50 were using metformin, 46 were using Glimepiride in addition to 50 apparently healthy non-diabetic matching for age and sex subjects have been tested as control group. EDTA anti-coagulated venous blood samples has been taken from eachsubject , platelet count and indices were measured using automatic blood counter (Sysmex KX-21N) and HbA1C was Measured using Ichroma II . Statistics was performed by SPSS (version 22). Results The results showed that both types of treatment (Metformin, Glimepiride)have reduced the platelets indices but the reduction in Glimepiride was insignificant except in PDW when comparedwith controls. Also both treatments have no effect on platelet count and there was insignificant variation between different doses of metformin and Glimepiride.Glimepiride diabetic patients from 15 to 20 yearshave increased platelet count in contrast to patients whom used glimepiride for less than 15 years.there was increased platelet count and decreased platelet indices in patients with foot ulcers whom using glimepiride than patients without complications. Also increased platelet indices in patients with HbA1C level less than 6% in contrast to those with HbA1C more than 7%. Conclusion It is concluded that both types of drugsreduce platelet indices. Glimepiride have a good prognostic effect on the Pro-thrombotic state and accelerated atherosclerosis which is associated with type 2 study population because the platelet indices were insignificant compared withcontrols. Keywords: Diabetes Mellitus, Metformin, Glimepiride, platelet count and indices